Ion-Exchange Processes in the Channels of Zeolites - Marsagishvili, T.; Machavariani, M.; Tatishvili, G.; Khositashvili, R.; Lekishvili, N. (Asian Journal of Chemistry, 2013)
Processes of non-adiabatic ion-exchange in the channels of zeolites have been considered. Calculations of rate constant of ion-exchange process in in the channels of zeolites, where one adsorbed particle is substituted for another, have been carried out. Analytical expressions for characteristic parameters of the process have been obtained.